170k views
14 votes
Use the chain rule to find the derivative of each of the following :

a.
(2)/((3x^2-x+7)^3)

b.
(4x-10)^1^0

1 Answer

9 votes

Answer:

see explanation

Explanation:

Using the chain rule

Given

y = f(g(x)), then


(dy)/(dx) = f'(g(x)) × g'(x)

(a)

y =
(2)/((3x^2-x+7)^3) = 2 (
3x^2-x+7)^(-3)


(dy)/(dx) = 2. - 3
(3x^2-x+7)^(-4) ×
(d)/(dx) (3x² - x + 7)

= - 6
(3x^2-x+7)^(-4) × (6x - 1)

=
(-6(6x-1))/((3x^2-x+7)^4)

---------------------------------------------------

(b)

y =
(4x-10)^(10)


(dy)/(dx) = 10
(4x-10)^(9) ×
(d)/(dx)(4x - 10)

= 10
(4x-10)^(9) × 4

= 40
(4x-10)^(9)

User Karthik Bollisetti
by
5.0k points